2011
DOI: 10.1007/s11099-011-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cold stress of young industrial chicory (Cichorium intybus L.) plants by chlorophyll a fluorescence imaging. I. Light induction curve

Abstract: Industrial chicory, Cichorium intybus L., is cultivated for the production of inulin. Most varieties of industrial chicory exhibit rather poor early growth, which limits further yield improvements in their European cultivation area. The poor early growth could be due to suboptimum adaptation of the gene pool to growth at low temperatures, sometimes in combination with high light intensities, which is typical of early-spring mornings. We have used chlorophyll (Chl) a fluorescence to evaluate the response of you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Our results clearly show that both MT and ML have a large impact on the Kautsky curve itself (Devacht et al 2011;part I) and the relaxation kinetics (this paper). This should be kept in mind when defining a procedure to estimate plant responses derived from Chl fluorescence measurements, but even more when comparing Chl fluorescence data obtained in growth chambers and those obtained under field conditions, where the light environment and temperature change continuously and at different temporal scales.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results clearly show that both MT and ML have a large impact on the Kautsky curve itself (Devacht et al 2011;part I) and the relaxation kinetics (this paper). This should be kept in mind when defining a procedure to estimate plant responses derived from Chl fluorescence measurements, but even more when comparing Chl fluorescence data obtained in growth chambers and those obtained under field conditions, where the light environment and temperature change continuously and at different temporal scales.…”
Section: Discussionsupporting
confidence: 66%
“…In the first part of this study (Devacht et al 2011), where the light-adapted state of the Kautsky curve was evaluated, we found that parameters such as the PSII operating efficiency (including PSII maximum efficiency and PSII efficiency factor) and NPQ are important to evaluate the effect of stress in terms of severity, processes that are affected, and acclimation to low GT. Analysis of the light-induction curves clearly demonstrated that young industrial chicory plants can adapt to low GT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, it is recognized that thylakoid membranes are the primary site of freezing damage in plant cells, thus affecting photosynthesis and CO2 fixation (Hincha et al 1996, Devacht et al 2011. Low temperatures always tend to inhibit electron transport via increased membrane viscosity through alterations in the biophysical properties of thylakoid lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Cold stress tolerance evaluations by means of CFI were reported in chicory (Cichorium intybus L.) [108,109]. In these studies, measurement of the induction and relaxation kinetics of the chlorophyll fluorescence in plants cultivated at different combinations of light intensities and temperatures were made through an imaging fluorescence system (CFImager, Technologica Ltd., Colchester, UK).…”
Section: Chlorophyll Fluorescence and Content Studiesmentioning
confidence: 99%